Flower Development Methods and Protocols - Riechmann, José Luis.; Riechmann, José Luis.; Wellmer, Frank.; Wellmer, Frank. (Methods in Molecular Biology, 2014)
In Flower Development: Methods and Protocols, researchers in the field detail protocols for  experimental approaches that are currently used to study the formation of flowers, from genetic methods and phenotypic analyses, to genome-wide experiments, modeling, and system-wide approaches. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls     Authoritative and practical, Flower Development: Methods and Protocols  is an essential guide for plant developmental biologists, from the novice to the experienced researcher, and for those considering venturing into the field.